Rainfall estimation from cloud-to-ground lightning data - João Victor Cal Garcia (2014)
The correlation between convective activity and the occurrence of lightning has been exploited in several works. The monitoring and tracking of convective activity is conventionally achieved by the use of weather radars, but many countries, like Brazil, lack an extensive coverage of such radars. On the other hand, Brazil has a network of lightning detectors that covers most of its territory and such detectors are quite less expensive than weather radars. Assuming that convective activity and lightning are correlated to some degree, lightning data is currently employed to monitor and track convective activity by means of the EDDA software in the Center for Natural Disasters Monitoring and Alert in Brazil. Besides this correlation, some works also address a quantitative relationship between the number of lightning and the precipitated mass. While some approaches were proposed to estimate rainfall using lightning data, they seem to have poor accuracy and to be limited to the same region and conditions where their specific parameters were obtained, limiting the application of lightning-estimated rainfall. This thesis proposes a new and more reliable approach to estimate the accumulated rainfall mass and distribution from lightning occurred in a preceding interval of time for a defined grid. The estimation of the rainfall mass is accomplished by a function inferred using grid points covered by weather radar data. This function is then mapped to the remaining grid points based on Brazilian rainfall statistics of recent years, making it applicable outside the range of weather radars. Rainfall spatial distribution is also estimated based on the density of occurrence of lightning. Rainfall estimation in this thesis is implemented by the Edda-chuva software that is being evaluated in the same center. Besides convective rainfall amount and distribution, the software presented in this thesis als o allows to estimate the amount and distribution of the total rainfall, including thus the stratiform rainfall. Test results show an improvement of the accumulated rainfall monitoring over most of the Brazilian territory covered by the network of electrical discharge detectors. RESUMO: A correlação entre a atividade convectiva e a ocorrência de descargas elétricas atmosféricas foi explorada em vários trabalhos. O monitoramento e rastreamento de atividade convectiva é convencionalmente feita por meio de radares meteorológicos, mas muitos países, como o Brasil, não têm uma extensa cobertura de tais radares. Por outro lado, o Brasil tem uma rede de detectores de descargas elétricas atmosféricas que cobre a maior parte de seu território e esses detectores são muito menos caros do que radares meteorológicos. Supondo-se que a atividade convectiva e descargas elétricas atmosféricas estejam correlacionadas em algum grau, dados de descarga elétrica são atualmente empregados para monitorar e rastrear a atividade convectiva por meio do software EDDA no Centro Nacional de Monitoramento e Alertas de Desastres Naturais (Cemaden), no Brasil. Além dessa correlação, alguns trabalhos também abordam uma relação quantitativa entre o número de descargas elétricas atmosféricas e a massa precipitada. Alguns trabalhos propuseram estimar precipitação a partir de dados de descargas, mas seus resultados foram imprecisos e limitados a mesma região e condições na qual foram obtidos, limitando o uso de precipitação estimada por descargas. Esta tese propõe uma nova metodologia para estimar a precipitação acumulada a partir do número de descargas ocorridas em um intervalo de tempo anterior para uma grade definida. Esta estimaçã é realizada por uma função inferida usando pontos de grade cobertos pelos dados de radar meteorológico e foi mapeada para os pontos de grade restantes com base em estatísticas de precipitação no Brasil para anos recentes, sendo utilizavel fora do alcance de radares meterorológicos. A distribuição espacial da precipitação também é estimada com base na densidade de ocorrência das descargas. A estimação de precipitação é implementada neste tese pelo software EDDA-chuva que está sendo avaliado no mesmo centro. Além da quantidade e distribuição da precipitação convectiva, o software permite estimar a quantidade e distribuição da precipitação total, incluindo portanto a precipitação estratiforme. Os resultados do teste mostram uma melhoria do monitoramento precipitação acumulada sobre a maior parte do território brasileiro coberto pela rede de detectores de descargas elétricas atmosféricas.